The concept of sex education for children and adolescents in Quranic perspective (comparative study of Abdullah Nashih Ulwan and Muhammad Quraish Shihab) - Salmah Febriani, Ina; Karolina, Asri; Shofwatul Millah, Siti (ATTARBIYAH: Journal of Islamic Culture and Education, 2024)
The purpose of this study is to conduct a comparative analysis between the views of Abdullah Nashih Ulwan and Muhammad Quraish Shihab on the concept of sex education for children and adolescents. This research uses a qualitative approach of library research type. The main data source is the book Tarbiyatul Aulad by Abdullah Nashih Ulwan and Sexuality and Interaction; Education from the Perspective of the Quran and Sunnah by Muhammad Quraish Shihab. The results showed that according to Abdullah Nashih Ulwan, sexuality education is categorized into four stages: tamyiz (7-10 years), murohaqoh (10-14 years), puberty (14-16 years), and post-baligh. Meanwhile, Muhammad Quraish Shihab emphasizes the importance of providing sex education as early as possible by explaining the differences in human sex and appreciating the discussion of sexuality. Muhammad Quraish Shihab divides three phases of sexual education. First, pre-baligh I (toddler phase/0-5 years). Second, pre-baligh II (child phase/6-11 years). Third, the baligh phase (adolescence/12-25 years). Finally, the post-baligh phase. This research contributes theoretically about the concept of sex education for children and adolescents.